A sprayable sound insulation and damping material and preparation method thereof

By using modified amylopectin and modified graphite in sprayable sound insulation damping materials, the materials have been solved, such as thermal stability, aging resistance and waterproofing at high temperatures, and low density, low VOC and excellent waterproofing are achieved. , aging resistance and corrosion resistance, meet the high-performance needs of the automotive industry.

CN118879144BActive Publication Date: 2025-02-11KEJIAN POLYMER MATERIALS (SHANGHAI) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411348260.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-02-11
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

Existing sprayable sound insulation damping materials show problems such as thermal stability, aging resistance and waterproofing in high temperature environments, and are highly dense and may release harmful gases, affecting driving stability and human health.

Method used

Modified amylopectin and modified graphite are used as main components, and the high temperature tolerance and waterproofing of the material are improved through the pre-gelatinization of modified starch and the grafting of organic compound molecular chains, and the multi-layer of modified graphite is improved. Cartridge structure and surface roughness, enhance the corrosion resistance and waterproofing of the material.

Benefits of technology

It realizes the performance of the material without cracking and bubbles at high temperatures of 140℃, maintains low density and extremely low VOC (volatile organic compounds), and significantly improves waterproof, aging resistance and corrosion resistance, meeting the automotive industry's High performance sprayable sound insulation damping material needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to the field of damping materials, and in particular to a sprayable sound insulation damping material and a preparation method thereof. The sprayable sound insulation damping material, in parts by mass, comprises the following raw materials: 20 to 30 parts of base emulsion, 0.1 to 0.8 parts of thickener, 1 to 2 parts of moisturizer, 0.2 to 0.6 parts of pH adjuster, 0.1 to 0.2 parts of mildew inhibitor, 2 to 6 parts of starch material, 50 to 65 parts of filler, 0.1 to 0.5 parts of foaming agent, 4 to 10 parts of water-based additive, and 5 to 10 parts of deionized water. The sprayable sound insulation damping material prepared in the present application can withstand high-temperature baking at 140°C without cracking or bubbling, and it has a low-density material and extremely low VOC, as well as being able to maintain good waterproof, aging-resistant, corrosion-resistant and other properties, effectively meeting the performance requirements of the automotive industry for sprayable sound insulation damping materials today, and has very excellent application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of damping materials, and in particular to a sprayable sound insulation damping material and a preparation method thereof. Background Art

[0002] Sprayable sound insulation and damping materials are commonly used to reduce structural vibration and noise transmission, especially in the automotive, aerospace and construction industries. These materials can be applied to various surfaces by spraying, providing good damping effect to reduce noise and vibration.

[0003] With the vigorous development of the automobile industry, the performance requirements for sprayable sound insulation and damping materials are becoming more diverse. Most of the damping sheets on cars today are asphalt damping sheets. Their high density increases the weight of the car, and they need to be cut into specific shapes before they can be attached to the sheet metal during construction. It is even difficult to ensure complete attachment in some specific locations. On the other hand, the performance of asphalt damping sheets is greatly affected by temperature; the performance decreases in high temperature environments, and they may harden in low temperature environments, affecting driving stability. In addition, asphalt damping sheets may release polycyclic aromatic hydrocarbons such as benzene, which can endanger human health.

[0004] In order to further meet the performance requirements of the automotive industry, researchers in the existing damping material industry are stepping up the research and development of high-performance sprayable sound insulation damping materials. However, there is no good solution to some difficult problems of high-performance sprayable sound insulation damping materials, such as thermal stability, aging resistance and waterproofness of damping materials at high temperatures, especially above 130°C.

[0005] Therefore, in order to solve the above problems, the present application provides a sprayable sound insulation and damping material and a preparation method thereof. The sprayable sound insulation and damping material prepared in the present application can withstand high-temperature baking at 140°C without cracking or bubbling, and has a low-density material and extremely low VOC, and can maintain good waterproof, aging-resistant, corrosion-resistant and other properties, effectively meeting the current performance requirements of the automotive industry for sprayable sound insulation and damping materials, and has very excellent application prospects. Summary of the invention

[0006] In order to solve the above problems, the first aspect of the present application provides a sprayable sound insulation and damping material. The raw materials, measured by mass, are: 20 to 30 parts of base emulsion, 0.1 to 0.8 parts of thickener, 1 to 2 parts of moisturizer, 0.2 to 0.6 parts of pH adjuster, 0.1 to 0.2 parts of mildewproofing agent, 2 to 6 parts of starch, 50 to 65 parts of filler, 0.1 to 0.5 parts of foaming agent, 4 to 10 parts of water-based additive, and 5 to 10 parts of deionized water.

[0007] As a preferred solution, the mass ratio of the base emulsion, thickener and starch material is (23~28): (0.1~0.6): (3~5).

[0008] As a preferred solution, the mass ratio of the base emulsion, thickener and starch material is (24~26): (0.2~0.5): (3~4).

[0009] As a preferred solution, the mass ratio of the base emulsion, the filler and the aqueous additive is (23-28): (55-64): (5.5-7).

[0010] As a preferred solution, the mass ratio of the base emulsion, the filler and the aqueous additive is (24-26): (58-62): (6-6.5).

[0011] As a preferred solution, the base emulsion is a damping emulsion.

[0012] As a preferred solution, the damping emulsion is an acrylic copolymer emulsion.

[0013] As a preferred solution, the thickener is at least one of polyacrylic acid, polyurethane, polyvinyl pyrrolidone, polyacrylamide, polyvinyl alcohol, and hydroxyethyl cellulose.

[0014] As a preferred solution, the thickener is polyacrylic acid; the polyacrylic acid is aqueous liquid polyacrylic acid.

[0015] As a preferred solution, the moisturizing agent is at least one of glycerol, propylene glycol, sorbitol, polyethylene glycol, diethylene glycol, and triethylene glycol.

[0016] As a preferred solution, the humectant is a combination of glycerol and sorbitol.

[0017] As a preferred solution, the mass ratio of glycerol to sorbitol is (4-5):(1-2).

[0018] As a preferred solution, the pH regulator is at least one of isopropanolamine, ammonia water, triethanolamine and dimethylethanolamine.

[0019] As a preferred solution, the pH regulator is isopropanolamine.

[0020] As a preferred solution, the mildew inhibitor is at least one of isothiazolinones, quaternary ammonium salts, organotin and organochlorine.

[0021] As a preferred solution, the mildew preventer is FY-8930 mildew preventer.

[0022] As a preferred solution, the starch material is a composition of straight-chain starch and modified amylopectin.

[0023] As a preferred solution, the mass ratio of the straight-chain starch to the modified amylopectin is (1-2): (4-6).

[0024] As a preferred solution, the mass ratio of the straight-chain starch to the modified amylopectin is (1.2-1.6): (4-4.5).

[0025] As a preferred solution, the straight chain content of the straight chain starch is ≥75%.

[0026] As a preferred scheme, the preparation method of the modified amylopectin comprises the following steps: S1: adding amylopectin to deionized water, stirring and mixing evenly, adjusting the pH to 9.2-9.6 with sodium hydroxide, then adding sodium perborate and mixing for 3-4 hours, centrifuging and filtering the product, washing it to obtain pretreated amylopectin; S2: adding the pretreated amylopectin to deionized water, heating it to 90-95°C, stirring and keeping it warm at 40-50rpm for 50-55min until gelatinization, then naturally cooling it to 60-80°C and adding an initiator, sodium hexametaphosphate, acrylamide, isobornyl acrylate and 2-ethylhexyl acrylate, stirring and keeping it warm at 60-80rpm for 3-5h, centrifuging, washing and freeze-drying it after the reaction is completed.

[0027] As a preferred solution, the mass ratio of the amylopectin to sodium perborate is (40-50): (4-5).

[0028] As a preferred solution, the mass ratio of the pretreated pullulan, sodium hexametaphosphate, acrylamide, isobornyl acrylate and 2-ethylhexyl acrylate is (50-60): (4-6): (10-15): (1-3): (1-3).

[0029] As a preferred solution, the mass ratio of the pretreated pullulan, sodium hexametaphosphate, acrylamide, isobornyl acrylate and 2-ethylhexyl acrylate is (52-55): (4-5): (12-14): (2-2.2): (1-1.5).

[0030] As a preferred solution, the initiator is potassium persulfate.

[0031] As a preferred solution, the branched chain content of the amylopectin is ≥65%.

[0032] The modified amylopectin added in the present application effectively improves the waterproof, aging and corrosion resistance and other properties of the sprayable sound insulation and damping material, and maintains good high temperature stability and storage stability. The modified branched starch added in the present application can greatly improve the high temperature tolerance of the starch material in the damping material by pre-gelatinization of the branched starch and subsequent grafting of the organic compound molecular chain, and by grafting the organic molecular chain, it can effectively form a good connecting force through its surface group and the modified graphite added in the present application, thereby assisting the modified graphite to be uniformly dispersed in the damping material to assume part of the carrier role, and can also play a role in connecting and fixing the modified graphite after the subsequent system is formed, thereby avoiding the segregation and free phenomenon of the filler particles in high temperature and long-term storage environment, and thus stably obtaining the high temperature resistance and waterproof properties imparted by the filling; on the other hand, the presence of a large number of branched chain segments can form a good three-dimensional network in the system, thereby forming a complex entangled structure of the molecular chain of the internal system, and the presence of this structure can cooperate with the modified graphite particles to greatly improve the steric hindrance of the internal system, greatly limit the free efficiency of free active molecules and the penetration rate of water molecules, thereby reducing the probability of active reactions and penetration effects within the system, thereby obtaining excellent stability, aging and corrosion resistance and other properties.

[0033] As a preferred solution, the filler is a composition of calcium carbonate and modified graphite.

[0034] As a preferred solution, the mass ratio of calcium carbonate to modified graphite is (4.2-4.6): (1.4-1.6).

[0035] As a preferred solution, the calcium carbonate is heavy calcium carbonate.

[0036] As a preferred solution, the average particle size of the calcium carbonate is 800-1600 mesh.

[0037] As a preferred scheme, the preparation method of the modified graphite comprises the following steps: S1: adding graphite to a mixed solvent of ethanol and deionized water, adding ammonia water to adjust the pH to 9.5-10, then adding ethyl orthosilicate, isopropanol and ethanol solution of triethanolamine, heating to 60-70°C, stirring and reacting at 50-60rpm for 1.5-2h, centrifuging, washing and drying the obtained product to obtain pretreated graphite; S2: adding the pretreated graphite to a mixed solvent of methanol and deionized water, ultrasonically dispersing at 200-300W for 30-40min, then transferring to a reaction container, heating to 55-60°C, adding a mixed aqueous solution of succinic anhydride, a coupling agent and zinc nitrate, and keeping warm for 2-2.5h; S3: then adding a mixed methanol solution of dimethylimidazole and silicon dioxide, heating to 65-70°C, stirring and reacting at 80-100rpm for 2-2.5h, and obtaining the product.

[0038] As a preferred solution, the graphite is flake graphite.

[0039] As a preferred solution, the average particle size of the graphite is 0.5-1.5 μm.

[0040] As a preferred solution, the mass ratio of graphite, tetraethyl orthosilicate, isopropyl alcohol and triethanolamine is (6-8): (1-1.4): (0.3-0.4): (0.1-0.2).

[0041] As a preferred solution, the mass ratio of the pretreated graphite, succinic anhydride and coupling agent is (5-5.5): (1.2-1.8): (0.2-0.4).

[0042] As a preferred solution, the mass ratio of the pretreated graphite, zinc nitrate, dimethylimidazole and silicon dioxide is (5-5.5): (1.4-1.6): (1-1.2): (0.2-0.3).

[0043] As a preferred solution, the average particle size of the silicon dioxide is 10-15 nm.

[0044] As a preferred solution, in the mixed solvent of ethanol and deionized water, the mass ratio of ethanol to deionized water is (1-1.5): (4-4.5).

[0045] As a preferred solution, in the mixed solvent of methanol and deionized water, the mass ratio of methanol to deionized water is (1-2): (1-2).

[0046] As a preferred solution, the coupling agent is 3-aminopropyltriethoxysilane.

[0047] The modified graphite added in this application can effectively improve the high temperature resistance and stability of the sprayable sound insulation and damping materials, and help maintain good waterproof and aging corrosion resistance. The modified graphite particles can use flake graphite as the base to form composite structure particles with multiple layers of mosaic particles on the surface. The existence of this structure can greatly improve its dispersion effect through the interaction between multiple active groups with the assistance of modified starch, thereby stably providing good heat resistance and stability. On the other hand, the graphite flakes can greatly enhance the continuous stacking effect of the composite structure particles in the system, thereby forming a good barrier structure for water molecules and free groups inside the system, greatly reducing their penetration and free speed, reducing the probability of contact between them, and thus reducing the possibility of internal active reactions. The surface can also form a surface rugged structure that isolates the aggregation of water molecules through the roughness of the surface of the graphite flakes, thereby obtaining excellent corrosion resistance, waterproof and other properties.

[0048] As a preferred solution, the foaming agent is at least one of sodium bicarbonate, azodicarbonamide or a polymer microsphere foaming agent.

[0049] As a preferred solution, the foaming agent is a polymer microsphere foaming agent.

[0050] As a preferred solution, the polymer microsphere foaming agent is an acrylic polymer microsphere foaming agent.

[0051] As a preferred solution, the aqueous auxiliary agent is a combination of an aqueous dispersant and an aqueous emulsifier.

[0052] As a preferred solution, the mass ratio of the aqueous dispersant to the aqueous emulsifier is (0.8-1):(5-6).

[0053] As a preferred solution, the aqueous dispersant is at least one of low molecular weight polyacrylates.

[0054] As a preferred solution, the aqueous emulsifier is at least one of aqueous emulsified waxes.

[0055] The second aspect of the present application provides a method for preparing the above-mentioned sprayable sound insulation and damping material, which specifically includes the following steps: S1: adding the base emulsion, deionized water and thickener into a container and stirring evenly, and then adding the moisturizer, pH adjuster and mildew inhibitor in sequence and stirring evenly; S2: after heating to 45~55°C, adding starch material, foaming agent and filler, and stirring at 60~80rpm for 1~2h; S3: after adding the aqueous additive, continue stirring until a dark gray uniform paste is formed.

[0056] The beneficial effects of this application are:

[0057] 1. A sprayable sound insulation and damping material provided in the present application can withstand high-temperature baking at 140°C without cracking or bubbling, and has a low-density material and extremely low VOC, and can maintain good waterproof, aging-resistant, corrosion-resistant and other properties, effectively meeting the current performance requirements of the automotive industry for sprayable sound insulation and damping materials, and has very excellent application prospects.

[0058] 2. A sprayable sound insulation and damping material provided in the present application, in which the modified branched starch is added, can greatly improve the high temperature tolerance of the starch material in the damping material by pre-gelatinization of the branched starch and subsequent grafting of the organic compound molecular chains, and through the grafting of the organic molecular chains, it can effectively form a good connecting force through its surface groups and the modified graphite added in the present application, thereby assisting the modified graphite to be uniformly dispersed in the damping material to assume part of the carrier role, and can also play a role in connecting and fixing the modified graphite after the subsequent system is formed, thereby avoiding the segregation and free phenomenon of the filler particles in high temperature and long-term storage environment, and thus stably obtaining the high temperature resistance and waterproof properties imparted by the filling.

[0059] 3. A sprayable sound insulation and damping material provided in the present application, the presence of a large amount of branched chain segments of modified amylopectin added can form a good three-dimensional network in the system, thereby forming a complex entangled structure of the molecular chains of the internal system. The existence of this structure can cooperate with the modified graphite particles to greatly improve the steric hindrance of the internal system, greatly limit the free efficiency of free active molecules and the penetration rate of water molecules, thereby reducing the probability of active reactions and penetration effects within the system, thereby obtaining excellent stability, aging and corrosion resistance and other properties.

[0060] 4. A sprayable sound insulation and damping material provided in the present application, wherein the modified graphite particles added therein can form composite structure particles with multi-layer mosaic particles on the surface with flaky graphite as the base. The existence of this structure can greatly improve its dispersion effect through the interaction force between multiple active groups with the assistance of modified starch, thereby stably providing good temperature resistance and stability. On the other hand, the graphite flakes can greatly enhance the continuous stacking effect of the composite structure particles in the system, thereby forming a good barrier structure for water molecules and free groups inside the system, greatly reducing their penetration and free speeds, reducing the probability of contact between them, and thereby reducing the possibility of internal active reactions. In addition, the surface roughness of the graphite flakes can also form a surface rugged structure that isolates the aggregation of water molecules, thereby obtaining excellent corrosion resistance, waterproofness and other properties. DETAILED DESCRIPTION

[0061] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.

[0062] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.

[0063] Example 1

[0064] Example 1 The first aspect provides a sprayable sound insulation and damping material. The raw materials, measured by mass, are: 25.8 parts of base emulsion, 0.5 parts of thickener, 1.1 parts of moisturizer, 0.3 parts of pH adjuster, 0.15 parts of mildewproofing agent, 3.6 parts of starch material, 59.8 parts of filler, 0.21 parts of foaming agent, 6.4 parts of water-based additive, and 4 parts of deionized water.

[0065] The base emulsion is a damping emulsion; the damping emulsion is an acrylic copolymer emulsion Accousticryl AV-1220 emulsion, which is purchased from Dow Chemical of the United States.

[0066] The thickener is a water-based liquid polyacrylic acid thickener purchased from Arkema, France, model VISCOATEX 730.

[0067] The moisturizing agent is a composition of glycerol and sorbitol, and the mass ratio of the two is 4.5:1.5.

[0068] The pH adjuster was isopropanolamine.

[0069] The mildew preventer was FY-8930 mildew preventer purchased from Nantong Broad Biochemical Co., Ltd.

[0070] The starch material is a composition of straight-chain starch and modified branched-chain starch, and the mass ratio of the two is 1.3:4.2.

[0071] The preparation method of modified amylopectin comprises the following steps, calculated by mass: S1: adding 48.5 parts of amylopectin to 160 parts of deionized water, stirring and mixing evenly, adjusting the pH to 9.5 with sodium hydroxide, then adding 4.8 parts of sodium perborate and mixing for 3.5 hours, centrifuging and filtering the product, washing it to obtain pretreated amylopectin; S2: adding 54 parts of pretreated amylopectin to 160 parts of deionized water, heating it to 90°C, stirring and keeping it warm at 50rpm for 50min until gelatinization, then naturally cooling it to 75°C and adding 0.12 parts of initiator, 4.5 parts of sodium hexametaphosphate, 13.8 parts of acrylamide, 2.1 parts of isobornyl acrylate and 1.2 parts of 2-ethylhexyl acrylate, stirring and keeping it warm at 80rpm for 4 hours, centrifuging, washing and freeze-drying it after the reaction is completed.

[0072] The linear content of amylose was 76.4%, and the branched content of amylopectin was 70.2%, both of which were purchased from the corresponding starch products sold by Wuhan Huaxiang Kejie Biotechnology Co., Ltd.

[0073] The initiator is potassium persulfate.

[0074] The filler is a composition of calcium carbonate and modified graphite, and the mass ratio of the two is 4.46:1.52.

[0075] The calcium carbonate is heavy calcium carbonate, and its average particle size is 1500 mesh.

[0076] The preparation method of modified graphite comprises the following steps, by weight: S1: adding 6.8 parts of graphite to a mixed solvent of ethanol and deionized water (a total of 100 parts, with a mass ratio of ethanol to deionized water of 1.5:4), adding ammonia water to adjust the pH to 9.8, then adding 1.2 parts of ethyl orthosilicate, 0.35 parts of isopropanol and 0.18 parts of an ethanol solution of triethanolamine, heating to 65°C, stirring at 60rpm for 1.5h, and centrifuging, filtering, washing and drying the obtained product to obtain pretreated graphite; S2: adding 5.2 parts of the pretreated graphite to methanol and The mixture was ultrasonically dispersed at 250W for 40 minutes in a mixed solvent of deionized water (100 parts in total, with a mass ratio of methanol to deionized water of 1:1), and then transferred into a reaction container and heated to 60°C. A mixed aqueous solution of 1.5 parts of succinic anhydride, 0.25 parts of 3-aminopropyltriethoxysilane and 1.55 parts of zinc nitrate (40 parts in total) was added and kept warm for 2.5 hours. S3: 1.18 parts of dimethylimidazole and 0.21 parts of a mixed methanol solution of silicon dioxide (30 parts in total) were then added, the temperature was raised to 70°C, and the reaction was stirred at 80rpm for 2.5 hours to obtain the product.

[0077] The graphite is flake graphite with an average particle size of 0.8 μm, purchased from Hebei Runhuabang New Material Technology Co., Ltd.; the average particle size of silicon dioxide is 12 nm.

[0078] The foaming agent is an acrylic polymer microsphere foaming agent, which is purchased from Akzo Nobel and is a foaming agent product of model Expancel 031WUF40.

[0079] The aqueous auxiliary agent is a composition of an aqueous dispersant and an aqueous emulsifier, and the mass ratio of the two is 0.9:5.5.

[0080] The aqueous dispersant is a sodium polyacrylate salt-soluble dispersant purchased from Shanghai Weiyong Industrial Co., Ltd. and sold as model D6601; the aqueous emulsifier is an aqueous emulsified wax WE-129B03 purchased from Shanghai Shunya Chemical Co., Ltd.

[0081] The second aspect of the present embodiment provides a method for preparing the above-mentioned sprayable sound insulation and damping material, which specifically includes the following steps: S1: adding the base emulsion, deionized water and thickener into the container and stirring evenly, and then adding the moisturizer, pH adjuster and mildew inhibitor in sequence and stirring evenly; S2: after heating to 50°C, adding starch material, foaming agent and filler, and stirring at 60rpm for 1.5h; S3: after adding the aqueous additive, continue stirring until a dark gray uniform paste is formed.

[0082] Example 2

[0083] Example 2 The first aspect provides a sprayable sound insulation and damping material. The raw materials, measured by mass, are: 23.8 parts of base emulsion, 0.3 parts of thickener, 1.1 parts of moisturizer, 0.3 parts of pH adjuster, 0.15 parts of mildewproofing agent, 3.8 parts of starch, 59.8 parts of filler, 0.19 parts of foaming agent, 6.4 parts of water-based additive, and 4 parts of deionized water.

[0084] The damping emulsion is an acrylic copolymer emulsion Accousticryl AV-1220 emulsion, which is purchased from Dow Chemical of the United States.

[0085] The thickener is a water-based liquid polyacrylic acid thickener purchased from Arkema, France, model VISCOATEX 730.

[0086] The moisturizing agent is a composition of glycerol and sorbitol, and the mass ratio of the two is 5:1.

[0087] The pH adjuster was isopropanolamine.

[0088] The mildew preventer was FY-8930 mildew preventer purchased from Nantong Broad Biochemical Co., Ltd.

[0089] The starch material is a composition of straight-chain starch and modified branched-chain starch, and the mass ratio of the two is 1.6:5.

[0090] The preparation method of modified amylopectin comprises the following steps, calculated by mass: S1: adding 48.5 parts of amylopectin to 160 parts of deionized water, stirring and mixing evenly, adjusting the pH to 9.5 with sodium hydroxide, then adding 4.8 parts of sodium perborate and mixing for 3.5 hours, centrifuging and filtering the product, washing it to obtain pretreated amylopectin; S2: adding 54 parts of pretreated amylopectin to 160 parts of deionized water, heating it to 90°C, stirring and keeping it warm at 50rpm for 50min until gelatinization, then naturally cooling it to 75°C and adding 0.12 parts of initiator, 4.5 parts of sodium hexametaphosphate, 13.8 parts of acrylamide, 2.1 parts of isobornyl acrylate and 1.2 parts of 2-ethylhexyl acrylate, stirring and keeping it warm at 80rpm for 4 hours, centrifuging, washing and freeze-drying it after the reaction is completed.

[0091] The linear content of amylose was 76.4%, and the branched content of amylopectin was 70.2%, both of which were purchased from the corresponding starch products sold by Wuhan Huaxiang Kejie Biotechnology Co., Ltd.

[0092] The initiator is potassium persulfate.

[0093] The filler is a composition of calcium carbonate and modified graphite, and the mass ratio of the two is 4.46:1.52.

[0094] The calcium carbonate is heavy calcium carbonate, and its average particle size is 1500 mesh.

[0095] The preparation method of modified graphite comprises the following steps, by weight: S1: adding 6.8 parts of graphite to a mixed solvent of ethanol and deionized water (a total of 100 parts, with a mass ratio of ethanol to deionized water of 1.5:4), adding ammonia water to adjust the pH to 9.8, then adding 1.2 parts of ethyl orthosilicate, 0.35 parts of isopropanol and 0.18 parts of an ethanol solution of triethanolamine, heating to 65°C, stirring at 60rpm for 1.5h, and centrifuging, filtering, washing and drying the obtained product to obtain pretreated graphite; S2: adding 5.2 parts of the pretreated graphite to methanol and The mixture was ultrasonically dispersed at 250W for 40 minutes in a mixed solvent of deionized water (100 parts in total, with a mass ratio of methanol to deionized water of 1:1), and then transferred into a reaction container and heated to 60°C. A mixed aqueous solution of 1.5 parts of succinic anhydride, 0.25 parts of 3-aminopropyltriethoxysilane and 1.55 parts of zinc nitrate (40 parts in total) was added and kept warm for 2.5 hours. S3: 1.18 parts of dimethylimidazole and 0.21 parts of a mixed methanol solution of silicon dioxide (30 parts in total) were then added, the temperature was raised to 70°C, and the reaction was stirred at 80rpm for 2.5 hours to obtain the product.

[0096] The graphite is flake graphite with an average particle size of 0.8 μm, purchased from Hebei Runhuabang New Material Technology Co., Ltd.; the average particle size of silicon dioxide is 12 nm.

[0097] The foaming agent is an acrylic polymer microsphere foaming agent, which is purchased from Akzo Nobel and is a foaming agent product of model Expancel 031WUF40.

[0098] The aqueous auxiliary agent is a composition of an aqueous dispersant and an aqueous emulsifier, and the mass ratio of the two is 1:5.4.

[0099] The aqueous dispersant is a sodium polyacrylate salt-soluble dispersant purchased from Shanghai Weiyong Industrial Co., Ltd. and sold as model D6601; the aqueous emulsifier is an aqueous emulsified wax WE-129B03 purchased from Shanghai Shunya Chemical Co., Ltd.

[0100] The second aspect of the present embodiment provides a method for preparing the above-mentioned sprayable sound insulation and damping material, which specifically includes the following steps: S1: adding the base emulsion, deionized water and thickener into the container and stirring evenly, and then adding the moisturizer, pH adjuster and mildew inhibitor in sequence and stirring evenly; S2: after heating to 50°C, adding starch material, foaming agent and filler, and stirring at 60rpm for 1.5h; S3: after adding the aqueous additive, continue stirring until a dark gray uniform paste is formed.

[0101] Example 3

[0102] Example 3 The first aspect provides a sprayable sound insulation and damping material. The raw materials, measured by mass, are: 23.2 parts of base emulsion, 0.2 parts of thickener, 1.1 parts of moisturizer, 0.3 parts of pH adjuster, 0.14 parts of mildewproofing agent, 3.4 parts of starch material, 59.8 parts of filler, 0.20 parts of foaming agent, 6.4 parts of water-based additive, and 5 parts of deionized water.

[0103] The damping emulsion is an acrylic copolymer emulsion Accousticryl AV-1220 emulsion, which is purchased from Dow Chemical of the United States.

[0104] The thickener is a water-based liquid polyacrylic acid thickener purchased from Arkema, France, model VISCOATEX 730.

[0105] The moisturizing agent is a composition of glycerol and sorbitol, and the mass ratio of the two is 5:1.

[0106] The pH adjuster was isopropanolamine.

[0107] The mildew preventer was FY-8930 mildew preventer purchased from Nantong Broad Biochemical Co., Ltd.

[0108] The starch material is a composition of straight-chain starch and modified branched-chain starch, and the mass ratio of the two is 1.6:5.

[0109] The preparation method of modified amylopectin comprises the following steps, calculated by mass: S1: adding 48.5 parts of amylopectin to 160 parts of deionized water, stirring and mixing evenly, adjusting the pH to 9.5 with sodium hydroxide, then adding 4.8 parts of sodium perborate and mixing for 3.5 hours, centrifuging and filtering the product, washing it to obtain pretreated amylopectin; S2: adding 54 parts of pretreated amylopectin to 160 parts of deionized water, heating it to 90°C, stirring and keeping it warm at 50rpm for 50min until gelatinization, then naturally cooling it to 75°C and adding 0.12 parts of initiator, 4.5 parts of sodium hexametaphosphate, 13.8 parts of acrylamide, 2.1 parts of isobornyl acrylate and 1.2 parts of 2-ethylhexyl acrylate, stirring and keeping it warm at 80rpm for 4 hours, centrifuging, washing and freeze-drying it after the reaction is completed.

[0110] The linear content of amylose was 76.4%, and the branched content of amylopectin was 70.2%, both of which were purchased from the corresponding starch products sold by Wuhan Huaxiang Kejie Biotechnology Co., Ltd.

[0111] The initiator is potassium persulfate.

[0112] The filler is a composition of calcium carbonate and modified graphite, and the mass ratio of the two is 4.46:1.52.

[0113] The calcium carbonate is heavy calcium carbonate, and its average particle size is 1500 mesh.

[0114] The preparation method of modified graphite comprises the following steps, by weight: S1: adding 6.8 parts of graphite to a mixed solvent of ethanol and deionized water (a total of 100 parts, with a mass ratio of ethanol to deionized water of 1.5:4), adding ammonia water to adjust the pH to 9.8, then adding 1.2 parts of ethyl orthosilicate, 0.35 parts of isopropanol and 0.18 parts of an ethanol solution of triethanolamine, heating to 65°C, stirring at 60rpm for 1.5h, and centrifuging, filtering, washing and drying the obtained product to obtain pretreated graphite; S2: adding 5.2 parts of the pretreated graphite to methanol and The mixture was ultrasonically dispersed at 250W for 40 minutes in a mixed solvent of deionized water (100 parts in total, with a mass ratio of methanol to deionized water of 1:1), and then transferred into a reaction container and heated to 60°C. A mixed aqueous solution of 1.5 parts of succinic anhydride, 0.25 parts of 3-aminopropyltriethoxysilane and 1.55 parts of zinc nitrate (40 parts in total) was added and kept warm for 2.5 hours. S3: 1.18 parts of dimethylimidazole and 0.21 parts of a mixed methanol solution of silicon dioxide (30 parts in total) were then added, the temperature was raised to 70°C, and the reaction was stirred at 80rpm for 2.5 hours to obtain the product.

[0115] The graphite is flake graphite with an average particle size of 0.8 μm, purchased from Hebei Runhuabang New Material Technology Co., Ltd.; the average particle size of silicon dioxide is 12 nm.

[0116] The foaming agent is an acrylic polymer microsphere foaming agent, which is purchased from Akzo Nobel and is a foaming agent product of model Expancel 031WUF40.

[0117] The aqueous auxiliary agent is a composition of an aqueous dispersant and an aqueous emulsifier, and the mass ratio of the two is 1:5.4.

[0118] The aqueous dispersant is a sodium polyacrylate salt-soluble dispersant purchased from Shanghai Weiyong Industrial Co., Ltd. and sold as model D6601; the aqueous emulsifier is an aqueous emulsified wax WE-129B03 purchased from Shanghai Shunya Chemical Co., Ltd.

[0119] The second aspect of the present embodiment provides a method for preparing the above-mentioned sprayable sound insulation and damping material, which specifically includes the following steps: S1: adding the base emulsion, deionized water and thickener into the container and stirring evenly, and then adding the moisturizer, pH adjuster and mildew inhibitor in sequence and stirring evenly; S2: after heating to 50°C, adding starch material, foaming agent and filler, and stirring at 60rpm for 1.5h; S3: after adding the aqueous additive, continue stirring until a dark gray uniform paste is formed.

[0120] Comparative Example 1

[0121] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the sprayable sound insulation and damping material, in parts by mass, has the following raw materials: 30.8 parts of base emulsion, 0.1 parts of thickener, 1.1 parts of moisturizer, 0.3 parts of pH adjuster, 0.15 parts of mildewproofing agent, 3.6 parts of starch material, 59.8 parts of filler, 0.21 parts of foaming agent, 6.4 parts of water-based additive, and 4 parts of deionized water.

[0122] The filler is a composition of calcium carbonate and modified graphite, and the mass ratio of the two is 5.06:0.92.

[0123] Comparative Example 2

[0124] The specific implementation of this comparative example is basically the same as that of Example 1, with the only difference being that the raw materials of the sprayable sound insulation and damping material, in parts by mass, are: 18.8 parts of base emulsion, 0.5 parts of thickener, 1.1 parts of moisturizer, 0.3 parts of pH adjuster, 0.15 parts of mildewproofing agent, 3.6 parts of starch material, 65.8 parts of filler, 0.21 parts of foaming agent, 6.4 parts of water-based additive, and 4 parts of deionized water.

[0125] The filler is a composition of calcium carbonate and modified graphite, and the mass ratio of the two is 2.86:3.72.

[0126] Comparative Example 3

[0127] The specific implementation of this comparative example is basically the same as that of Example 1, with the only difference being that the raw materials of the sprayable sound insulation and damping material, in parts by mass, are: 35.8 parts of base emulsion, 0.5 parts of thickener, 1.1 parts of moisturizer, 0.3 parts of pH adjuster, 0.15 parts of mildewproofing agent, 3.6 parts of starch material, 25.5 parts of filler, 0.21 parts of foaming agent, 6.4 parts of water-based additive, and 4 parts of deionized water.

[0128] Comparative Example 4

[0129] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of modified amylopectin comprises the following steps, calculated by mass: S1: adding 60.5 parts of amylopectin to 160 parts of deionized water, stirring and mixing, adjusting the pH to 9.5 with sodium hydroxide, then adding 1.9 parts of sodium perborate and mixing for 3.5 hours, centrifuging and filtering the product, washing it to obtain pretreated amylopectin; S2: adding 54 parts of pretreated amylopectin to 160 parts of deionized water, heating it to 90°C, stirring and keeping it warm at 50rpm for 50min until gelatinization, then naturally cooling it to 75°C and adding 0.12 parts of initiator, 4.5 parts of sodium hexametaphosphate, 13.8 parts of acrylamide, 2.1 parts of isobornyl acrylate and 1.2 parts of 2-ethylhexyl acrylate, stirring and keeping it warm at 80rpm for 4 hours, centrifuging, washing and freeze-drying it after the reaction is completed.

[0130] Comparative Example 5

[0131] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of modified amylopectin comprises the following steps, calculated by mass: S1: adding 48.5 parts of amylopectin to 160 parts of deionized water, stirring and mixing, adjusting the pH to 9.5 with sodium hydroxide, then adding 4.8 parts of sodium perborate and mixing for 3.5 hours, centrifuging and filtering the product, washing it to obtain pretreated amylopectin; S2: adding 54 parts of pretreated amylopectin to 160 parts of deionized water, heating it to 90°C, stirring and keeping it warm at 50rpm for 50min until gelatinization, then naturally cooling it to 75°C and adding 0.12 parts of initiator, 1.5 parts of sodium hexametaphosphate, 25.8 parts of acrylamide, 0.8 parts of isobornyl acrylate and 0.2 parts of 2-ethylhexyl acrylate, stirring and keeping it warm at 80rpm for 4 hours, centrifuging, washing and freeze-drying it after the reaction is completed.

[0132] Comparative Example 6

[0133] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of modified graphite comprises the following steps, by weight: S1: adding 8.8 parts of graphite to a mixed solvent of ethanol and deionized water (a total of 100 parts, the mass ratio of ethanol to deionized water is 1.5:4), adding ammonia water to adjust the pH to 9.8, then adding 0.6 parts of ethyl orthosilicate, 0.15 parts of isopropanol and 0.06 parts of an ethanol solution of triethanolamine, heating to 65°C, stirring at 60rpm for 1.5h, and centrifuging, filtering, washing and drying the obtained product to obtain pretreated graphite; S2: adding 5 .2 parts of pretreated graphite are added to a mixed solvent of methanol and deionized water (a total of 100 parts, the mass ratio of methanol to deionized water is 1:1), ultrasonically dispersed at 250W for 40 minutes, then transferred to a reaction container, heated to 60°C, and added with a mixed aqueous solution of 1.5 parts of succinic anhydride, 0.25 parts of 3-aminopropyltriethoxysilane and 1.55 parts of zinc nitrate (a total of 40 parts), and kept warm for 2.5 hours; S3: Then, a mixed methanol solution of 1.18 parts of dimethylimidazole and 0.21 parts of silicon dioxide (a total of 30 parts) is added, the temperature is raised to 70°C, and the reaction is kept warm and stirred at 80rpm for 2.5 hours to obtain S3.

[0134] Comparative Example 7

[0135] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of modified graphite comprises the following steps, by mass: S1: adding 6.8 parts of graphite to a mixed solvent of ethanol and deionized water (a total of 100 parts, with a mass ratio of ethanol to deionized water of 1.5:4), adding ammonia water to adjust the pH to 9.8, then adding 1.2 parts of ethyl orthosilicate, 0.35 parts of isopropanol and 0.18 parts of an ethanol solution of triethanolamine, heating to 65°C, stirring at 60rpm for 1.5h, and centrifuging, filtering, washing and drying the obtained product to obtain pretreated graphite; S2: 8.5 parts of pretreated graphite were added to a mixed solvent of methanol and deionized water (a total of 100 parts, with a mass ratio of methanol to deionized water of 1:1), and ultrasonically dispersed at 250W for 40 minutes. Then, the mixture was transferred to a reaction vessel and heated to 60°C, and a mixed aqueous solution of 1.2 parts of succinic anhydride, 0.11 parts of 3-aminopropyltriethoxysilane and 1.1 parts of zinc nitrate (a total of 40 parts) was added, and the mixture was kept warm for 2.5 hours. S3: Then, a mixed methanol solution of 0.8 parts of dimethylimidazole and 0.1 parts of silicon dioxide (a total of 30 parts) was added, the temperature was raised to 70°C, and the mixture was kept warm and stirred at 80rpm for 2.5 hours to obtain the product.

[0136] Comparative Example 8

[0137] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the graphite is flake graphite with an average particle size of 5.5 μm, purchased from Hebei Runhuabang New Material Technology Co., Ltd.; and the average particle size of silicon dioxide is 38 nm.

[0138] Performance Evaluation

[0139] The sprayable sound insulation and damping materials prepared in the examples and comparative examples were subjected to performance tests after use, and the results are recorded in Tables 1 and 2.

[0140] Test items:

[0141] Appearance: After curing, the dry film has no holes, cracks, or bubbles.

[0142] Rotational viscosity: refer to GB / T 2794-1995, rotor No. 7, speed is 20r / min.

[0143] Wet film density: refer to GB / T 13354-1992, using density cup.

[0144] Curing conditions: Refer to GB / T 1728-1989, fully cured at 140℃ for 20min, no stickiness on the surface.

[0145] Non-volatile matter content: refer to GB / T 2793-1995.

[0146] Adhesion: The test plate size is 150mm×70mm×0.8mm. The test material is coated into a shape of 80mm long, 40mm wide, and 2mm slope. The surface is scraped flat and the test piece is kept in an oven at (140±2)℃ for 20min. After taking it out, place it at room temperature for 24h, and cut two parallel lines on the test piece with a razor blade, with a distance of 5mm between the two lines. The cutting force should be uniform and moderate, so that the blade edge can just penetrate the coating and touch the substrate during cutting, and then the coating is evenly peeled off from the thicker end. The peeling results are graded according to the following levels to distinguish different adhesion effects: Level 1: The residual coating area on the test plate is less than 60%; Level 2: The residual coating area on the test plate is ≥60%; Level 3: The residual coating area on the test plate is ≥70%; Level 4: The residual coating area on the test plate is ≥80%; Level 5: The residual coating area on the test plate is ≥90%.

[0147] Flowability: Vertical flow: The test plate size is (300×100×0.8) mm, the width of one end of the test sample is 50 mm, and the rest of the area is coated with water-based damping paint with a coating thickness of 3 mm, and the cover is removed immediately. With the original covered area facing downward, the sample is placed vertically for 30 minutes in the standard environment of the laboratory, and the sagging of the paint is measured and recorded. Back flow: The test plate size is (300×100×0.8) mm, the width of both ends of the test sample is 50 mm, and the rest of the area is coated with water-based damping paint with a coating thickness of 3 mm, and the cover is removed immediately. With the paint facing downward, the sample is placed vertically for 30 minutes in the standard environment of the laboratory, and observe whether there is dripping. Keep this state unchanged, put it in an oven at (140±2)℃ for 20 minutes, and observe whether there is dripping or deformation after taking it out.

[0148] Volume expansion rate: The test plate size is in accordance with the specification requirements of 150×70×0.8mm. The width of one end of the test specimen is covered with 20mm, and the remaining area is coated with water-based damping coating with a coating thickness of 3mm. After removing the covering, it is baked in an oven at (140±2)℃ for 20min for curing. The test piece is placed in the standard laboratory environment for 24h, and a vernier caliper is used to measure the changes in the coating in the middle of the test piece. The coating thickness and volume expansion rate are measured and calculated.

[0149] Low temperature drop ball impact: Select an electrophoresis plate with a specification of 100×200×0.8mm, and apply a water-based damping coating with an area of ​​160mm×70mm×3mm on the electrophoresis plate. The prepared sample should be cured under baking conditions of 130℃ / 20min, 140℃ / 20min, and 170℃ / 20min respectively. After cooling in the standard environment of the laboratory, place the sample to be tested at -40℃ for 6h. After the test, quickly take out the sample, fix the sample on a suitable fixture with the coated side facing down, and clamp the edges of the sample. Use a steel ball weighing 250g (diameter 39.4mm) to impact the center of the back of the sample in a free fall from a height of 400mm from the sample. Cracks in the coating are acceptable, but peeling or separation from the substrate is unacceptable.

[0150] Damping coefficient: refer to GB / T 18258-2000, follow the requirements of test plate b, and take the damping coefficient of the second-order resonance peak.

[0151] Shelf life: Place at room temperature and visually inspect for abnormal conditions such as stratification or water seepage, and the storage time until the abnormal condition occurs.

[0152] Waterproofness - water contact angle: The sessile drop method is used to test the water contact angle of the material surface. The test water drop is 2 μL and the test time is 15 s.

[0153] Aging resistance: Store the samples in a constant temperature and humidity chamber at 68±3℃ and relative humidity 75±3%.

[0154]

[0155]

[0156]

[0157]

[0158] It can be seen from the data results of the embodiments and comparative examples of the present application and Table 1 and Table 2 that embodiments 1 to 3 of the present application have obvious advantages over comparative examples 1 to 8 in terms of high temperature stability, damping effect, water resistance and aging corrosion resistance. This is mainly due to the combined effect of the modified starch, modified filling particles and other matching schemes specified in the present application. Comparative examples 1 to 8 did not adopt the technical scheme specified in the present application, resulting in obvious disadvantages in the above-mentioned performance tests. This further proves the necessity of the technical scheme specified in the present application for the technical effect of the present application and solving technical problems.

Claims

1. A sprayable sound insulation and damping material, characterized in that: The raw materials are as follows: 20-30 parts of base emulsion, 0.1-0.8 parts of thickener, 1-2 parts of moisturizer, 0.2-0.6 parts of pH adjuster, 0.1-0.2 parts of mildewproof agent, 2-6 parts of starch material, 50-65 parts of filler, 0.1-0.5 parts of foaming agent, 4-10 parts of water-based additive, and 5-10 parts of deionized water. The mass ratio of the base emulsion, thickener and starch material is (23-28): (0.1-0.6): (3-5); The mass ratio of the base emulsion, filler and aqueous additive is (23-28): (55-64): (5.5-7); The base emulsion is a damping emulsion; the damping emulsion is an acrylic copolymer emulsion; The thickener is at least one of polyacrylic acid, polyurethane, polyvinyl pyrrolidone, polyacrylamide, polyvinyl alcohol, and hydroxyethyl cellulose; The moisturizing agent is at least one of glycerol, propylene glycol, sorbitol, polyethylene glycol, diethylene glycol, and triethylene glycol; The pH regulator is at least one of isopropanolamine, ammonia, triethanolamine, and dimethylethanolamine; The mildew inhibitor is at least one of isothiazolinone, quaternary ammonium salt, organotin and organochlorine; The starch material is a composition of amylose and modified amylopectin; the mass ratio of amylose to modified amylopectin is (1-2):(4-6); The linear content of the amylose is ≥75%; the branched content of the amylopectin is ≥65%; The preparation method of modified amylopectin comprises the following steps: S1: adding amylopectin to deionized water, stirring and mixing evenly, adjusting the pH to 9.2-9.6 with sodium hydroxide, then adding sodium perborate and mixing for 3-4 hours, centrifuging and filtering the product, washing it to obtain pretreated amylopectin; S2: adding the pretreated amylopectin to deionized water, heating it to 90-95° C., stirring and keeping it warm at 40-50 rpm for 50-55 minutes until gelatinization, then naturally cooling it to 60-80° C., adding an initiator, sodium hexametaphosphate, acrylamide, isobornyl acrylate and 2-ethylhexyl acrylate, stirring and keeping it warm at 60-80 rpm for 3-5 hours, centrifuging, washing, and freeze-drying it after the reaction is completed to obtain the modified amylopectin; The mass ratio of pullulan and sodium perborate is (40-50): (4-5); The mass ratio of the pretreated pullulan, sodium hexametaphosphate, acrylamide, isobornyl acrylate and 2-ethylhexyl acrylate is (50-60): (4-6): (10-15): (1-3): (1-3); The filler is a composition of calcium carbonate and modified graphite; the mass ratio of calcium carbonate to modified graphite is (4.2-4.6): (1.4-1.6); The calcium carbonate is heavy calcium carbonate; the average particle size of the calcium carbonate is 800-1600 mesh; The preparation method of the modified graphite comprises the following steps: S1: adding graphite to a mixed solvent of ethanol and deionized water, adding ammonia water to adjust the pH to 9.5-10, then adding ethyl orthosilicate, isopropanol and ethanol solution of triethanolamine, heating to 60-70°C, stirring and reacting at 50-60rpm for 1.5-2h, centrifuging, filtering, washing and drying the obtained product to obtain pretreated graphite; S2: adding the pretreated graphite to a mixed solvent of methanol and deionized water, ultrasonically dispersing at 200-300W for 30-40min, then transferring to a reaction container, heating to 55-60°C, adding a mixed aqueous solution of succinic anhydride, a coupling agent and zinc nitrate, and keeping warm for 2-2.5h; S3: then adding a mixed methanol solution of dimethylimidazole and silicon dioxide, heating to 65-70°C, stirring and reacting at 80-100rpm for 2-2.5h, and obtaining the product; The mass ratio of graphite, tetraethyl orthosilicate, isopropyl alcohol and triethanolamine is (6-8): (1-1.4): (0.3-0.4): (0.1-0.2); The mass ratio of the pretreated graphite, succinic anhydride and coupling agent is (5-5.5): (1.2-1.8): (0.2-0.4); The mass ratio of the pretreated graphite, zinc nitrate, dimethylimidazole and silicon dioxide is (5-5.5): (1.4-1.6): (1-1.2): (0.2-0.3); The graphite is flake graphite; the average particle size of the graphite is 0.5-1.5 μm; The aqueous auxiliary agent is a composition of an aqueous dispersant and an aqueous emulsifier; The mass ratio of the aqueous dispersant to the aqueous emulsifier is (0.8-1):(5-6).

2. The sprayable sound insulation and damping material according to claim 1, characterized in that: The thickener is polyacrylic acid; the polyacrylic acid is aqueous liquid polyacrylic acid.

3. The sprayable sound insulation and damping material according to claim 2, characterized in that: The moisturizing agent is a composition of glycerol and sorbitol; the mass ratio of glycerol to sorbitol is (4-5): (1-2).

4. The sprayable sound insulation and damping material according to claim 3, characterized in that: The pH regulator is isopropanolamine.

5. A method for preparing the sprayable sound insulation and damping material according to any one of claims 1 to 4, characterized in that: The specific steps include: S1: Add the base emulsion, deionized water and thickener into the container and stir evenly, then add the moisturizer, pH adjuster and mildew inhibitor in turn and stir evenly; S2: After heating to 45-55°C, add starch, foaming agent and filler, and stir at 60-80rpm for 1-2h; S3: After adding the water-based additive, continue stirring until a dark gray uniform paste is formed.

Citation Information

Patent Citations

  • Modified amylopectin material, preparation method thereof and water-based ink containing same

    CN108610739A

  • High-performance environment-friendly water-based damping coating and preparation method thereof

    CN118374194A